Event Operation and Management in Risk Assessment for Outdoor Food Bazaar Events - Sari , Afita; Sooai , Anastasia S.E; Rahmawati , Fadila; Saputra, Fajar; Silitonga, Laura Julige; Santoso, Nanda Putri; Tambunan, Jessica (Universitas Prasetiya Mulya, 2024)
This study evaluates risk management in organizing a food bazaar held in an open field at the Jakarta International Velodrome from May 31 to June 2, 2024. The research methodology includes direct observation, structured interviews with the organizing committee, and document analysis. The assessment results indicate that the event falls into the Very High Risk category for safety aspects, with potential hazards such as smuggling, theft, and fire. Additionally, the cleanliness of the area and healthcare facilities are deemed inadequate, categorized as High Risk. The limitations of hygiene facilities such as toilets and sinks, as well as the risk of dehydration, were also identified. This study recommends enhanced preparation and attention to risk management for similar events in the future to ensure the safety and comfort of visitors. By identifying, analyzing, and evaluating risks more comprehensively, it is hoped that event organizers can minimize potential hazards and improve the quality of future events. The study also emphasizes the importance of collaboration among various stakeholders, including the government, event organizers, security personnel, and healthcare services, to create a safe and comfortable event environment. Measures such as safety training for staff, adequate placement of healthcare facilities, and improved security systems can reduce the risks faced by visitors. Additionally, the study highlights the need for effective communication with the audience regarding safety and health protocols to be followed during the event. The implementation of technology such as crowd monitoring applications and early detection systems can also be a solution in managing risks more effectively.